Effects on Morphometry of Small Intestine of Broiler (Gallus domesticus) by Using Various Feed Additives - Saini, Jyoti (Indian Journal of Veterinary Anatomy, 2018)
An experiment was conducted using 350 one-day old unsexed (Cobb 400) broiler chickens to study the effect of dietary supplementation of various feed additives on morphometric characteristics of small intestine. Experimental treatments were: 1) control, 2) control + cocktail enzymes, 3) control + prebiotic, 4) control + probiotic, 5) control + organic acid 6) control + antioxidant and 7) control + saponin and inulin. Results showed that body weight, small intestine weight, relative weight (%), small intestine length, weight to length ratio were significantly improved by the supplementation of feed additives (P